2019
DOI: 10.1680/jgeot.17.p.201
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear rocking stiffness of embedded foundations in sand

Abstract: The rocking response of embedded foundations in sand is studied, combining centrifuge modelling and numerical analysis. In total, 51 centrifuge model tests are conducted at ETH Zurich, varying the embedment ratio D/B and the factor of safety against vertical loading (bearing capacity), Fs. The experimental results are used to validate three-dimensional finite-element models, which are subsequently employed for a parametric study. The initial two phases of non-linear response are studied, namely quasi-elastic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…On the other hand, foundation uplift causes a larger dissipation of energy and prevents the elements of the superstructure from yielding when there is a seismic force applied to the structure. Based on the experimental and numerical studies, several researchers [16][17][18][19][20][21][22][23][24] have suggested that rocking foundation has self-centring ability, elongates the structure period during excitation, and reduces the demands on the superstructure. Subsequently, simplified methods to predict the nonlinear rocking stiffnesses were provided [25][26][27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, foundation uplift causes a larger dissipation of energy and prevents the elements of the superstructure from yielding when there is a seismic force applied to the structure. Based on the experimental and numerical studies, several researchers [16][17][18][19][20][21][22][23][24] have suggested that rocking foundation has self-centring ability, elongates the structure period during excitation, and reduces the demands on the superstructure. Subsequently, simplified methods to predict the nonlinear rocking stiffnesses were provided [25][26][27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
“…Giouvanidis and Dong [8] compared the results of the conventional design approaches of bridge columns with design approaches that consider rocking isolation effects. Different researchers used shaking table tests to investigate the behavior of rocking foundations on sands [9][10][11] while, for better simulation of stress distribution of models, some other researchers employed centrifuge tests to investigate the behavior of rocking foundations [12][13][14][15][16][17]. Kim et al [18] and Liu et al [19] used centrifuge tests to investigate the behavior of low rises buildings with rock foundations.…”
Section: Introductionmentioning
confidence: 99%
“…Deng (2012) and Deng et al (2014) introduced a trilinear moment-rotation model for the nonlinear foundations consisted of an elastic and a plastic element in series so that the elastic element stiffness was the initial stiffness and the equivalentlinear stiffness of the plastic element was equal to the secant stiffness regarding maximum rotation and moment capacity of foundation. Taeseri et al (2019) emphasized the shortcomings of the existing impedance formulations, e.g., Gazetas (1991) in considering soil inhomogeneity and addressed its effects on the small strain rocking stiffness of embedded foundations. In line with the simplified methods, Sieber et al (2020) investigated a nonlinear and a bilinear rocking stiffness model for simulation of bridge piers with square foundations on stiff clay and observed such simplified models were appropriate for the maximum rotation prediction while not for the rotation time history and M-θ loops.…”
Section: Introductionmentioning
confidence: 99%